2021
DOI: 10.3390/ma14092255
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Mechanical and Physical Behavior of Gypsum Boards with Plastic Cable Waste Aggregates and Their Application to Construction Panels

Abstract: The objective of this study was to analyze the physico-mechanical properties of gypsum boards including plastic waste aggregates from cable recycling. The plastic cable waste is incorporated into the gypsum matrix without going through any type of selection and/or treatment, as it is obtained after the cable recycling process. In the experimental process, gypsum boards of different dimensions were manufactured and tested for their Young’s modulus, shock-impact resistance, flexural strength, thermal conductivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 32 publications
(44 reference statements)
2
7
0
Order By: Relevance
“…The storage of the samples also complied with the standard UNE EN 13279-2 [23]. The main mechanical and hygrothermal properties of these new materials, as well as their fire behaviour, can be found in previous studies [24][25][26][27].…”
Section: Methodsmentioning
confidence: 99%
“…The storage of the samples also complied with the standard UNE EN 13279-2 [23]. The main mechanical and hygrothermal properties of these new materials, as well as their fire behaviour, can be found in previous studies [24][25][26][27].…”
Section: Methodsmentioning
confidence: 99%
“…According to the authors, the presence of recycled ceramic tile powder enhanced mass loss, decreasing thermal conductivity. In another study, Vidales-Barriguete et al [83] added plastic cable waste to replace gypsum binder and the results showed that the thermal properties improved slightly with up to 60% of waste incorporation. Some authors studied the incorporation of waste as an additive into mortars [36,55,66].…”
Section: Thermal Performancementioning
confidence: 99%
“…Mechanical strength and bulk density of gypsum composites with plastic waste: Reference is a plaster with a water/gypsum ratio of 0.7 by weight [24]; PP is polypropylene waste from coffee capsules [25]; EPS and XPS are expanded and extruded polystyrene waste, respectively [18]; Pipe foam insulation shredded in average diameter of 2.5 mm [26]; Plastic cable is shredded waste from low voltage cable sheaths [27]; Polycarbonate [28]; CD and DVD are shredded and screened waste [15]; LDPE is recycled low density polyethylene [29]; ELT-rubber is granulated rubber from disused tyres of average diameter 2.5 mm [30]; SAP (superabsorbent polymer) is 15 g additions of sodium polyacrylate [24].…”
Section: Figurementioning
confidence: 99%